THE IMPORTANCE OF CULTURE CONDITIONS IN FERMENTATION OF STREP-TOMYCES SPECTABILIS (Scientific journal of the Fergana State University, 2026)
To enhance the prоductiоn of biologically active compounds by the Streptomyces spectabilis strain, cultivation conditions were optimized, and the strain’s morphological chаracteristics were examined microscopically across various ISP (International Streptomyces Project) nutrient media. Streptomyces spectabilis is a microorganism known for producing multiple antibiotics and holds significant importance in medicine and the pharmaceutical industry.